The protective effects of gastrodin on neurological disorders: an update and future perspectives - Shi, Zhouying; Zhang, Yali; Xiao, Yuhua; Shi, Zhoujing; Wei, Xiaotong; Wang, Bin; Yuan, Yue; Li, Ping (Frontiers in Pharmacology, 2024)
Neurological disorders are characterized by high mortality and disability rates. Furthermore, the burden associated with disability and mortality resulting from neurological disorders has been increasing at an alarming rate. Botanical drugs and their bioactive components have emerged as a prominent area of research, offering a promising avenue for developing novel alternatives for treating neurological diseases. Gastrodin is the principal active component derived from the traditional Chinese medicinal plant Gastrodia elata Blume (GEB). Existing literature reveals that gastrodin exerts various pharmacological protective actions against neurological disorders. This review aimed to collate novel literature on gastrodin for treating neurological disorders from Web of Science, PubMed, Embase and CNKI. The pharmacokinetics of gastrodin, its therapeutic role in neurological disorders, the main mechanisms of action and clinical application were addressed. Furthermore, a detailed overview of gastrodin drug delivery systems and physical enhancement methods was presented, offering invaluable insights into potential research and the extensive applications of gastrodin.